A Scientometric Overview of Global Dinoflagellate Research - Carlos Yure B. Oliveira; Cicero Diogo L. Oliveira; Marius N. Müller; Elizabeth P. Santos; Danielli M. M. Dantas; Alfredo O. Gálvez (Publications, 2020)
Understanding the evolution of scientific literature is a critical and necessary step for the development and strengthening of a research field. However, an overview of global dinoflagellate research remains unavailable. Herein, global dinoflagellate research output was analyzed based on a scientometric approach using the Scopus data archive. The basic characteristics and worldwide interactions of dinoflagellate research output were analyzed to determine the temporal evolution and new emerging trends. The results confirm that dinoflagellate research output, reflected in the number of publications, is a fast-growing area since the mid-1990s. In total, five research subareas emerged using a bibliometric keywords analysis: (1) “symbiosis with coral reefs”, (2) “phylogeny”, (3) “palynology”, (4) “harmful algal blooms” and (5) “nutrition strategies”. Dinoflagellate publications were modeled by fish production (both aquaculture and fisheries) and economic and social indexes. Finally, directions for future research are proposed and discussed. The presented scientometric analysis confirms that dinoflagellate research is an active and important area with focus on mitigating economic impacts, especially in regard to fish production.